PENGARUH PROFESIONALITAS, KETAATAN PADA KODE ETIK, DAN PENGALAMAN AUDITOR TERHADAP PENENTUAN TINGKAT MATERIALITAS - Robinson, Robinson (BISNIS, 2014)
The purpose of this research is the first,  provide empirical evidence o f the influence of professionalism auditor against consideration the level of materiality, adherence to a code of ethics to the level of materiality considerations, the level of experience of the auditor's consideration of materiality, and provide empirical evidence of the influence of auditor professionalism, adherence to a code of ethics, and experience of the auditor on consideration of materiality levels.The results showed that: 1) Professionalism Auditor (X1) had no significant effect on the Consideration of Materiality level, which is indicated by a significance value of 0.154; 2) Adherence to the Code of Ethics (X2) has a significant influence on consideration Materiality level, which indicated by a significance value of 0.008; 3) experience Auditor (X3) have no significant influence on consideration Materiality level, indicated by a significance value of 0.819,  and  4)  Auditor  professionalism,  adherence  to  the  Code  of  Ethics  and  Auditor experience together has influence consideration of Materiality significant level, which is indicated by the significant value of 0.000.